Evaluation of four different surface sampling techniques for microbes on three different food preparation surfaces - DeGeer, Staci Lynn (Kansas State University, 2009)
There are many different environmental sampling methods that are currently used in the industry. They include swab, sponge, flocked swab, direct agar contact, and M-Vac. Several studies have been conducted to determine the benefits and drawbacks of each method. Sampling methods utilized in this study were the swab, flocked swab, and M-Vac. Three surfaces were utilized in this study: ultra high density polypropylene, 304 stainless steel with a 2B finish, and 304 stainless steel with a 2B finish and a buffed surface. Surfaces sampled were 100 cm2. Prior to inoculation, surfaces were autoclaved for 15 min at 121 °C for sterilization. Surfaces were inoculated by either Listeria monocytogenes or Escherichia coli O157:H7 at a concentration of 9 log10 CFU/ml by painting the inoculum onto the surface with a sterilized paintbrush. Brushes were dipped in inoculum for 2 sec before painting from left to right once and then from up to down once. Brushes were redipped for 2 sec and the painting step was repeated. The same brush was used for all E. coli O157:H7 samples and a different brush was used for all L. monocytogenes samples. Then, the surfaces were allowed to dry for 30 min before sampling took place. Listeria monocytogenes samples were appropriately diluted and plated in duplicate onto Tryptic Soy Agar (TSA) and Modified Oxford Media (MOX). Escherichia coli O157:H7 samples were properly diluted and plated in duplicate onto TSA and MacConkey Sorbital Agar (MSA). After plating, dry surfaces were stained using LIVE/DEAD® BacLight™ Bacterial Viability Kit. The Zeiss LSM 5 Pascal confocal laser scanning electron microscope was used for microscopy images and photographs. Six 1 mm by 1 mm random and representative images were taken of each surface. Viable cell count results show that the sponge sampling method, in general, recovered a higher number of microorganisms. The swab was normally shown to recover the least number of microorganisms. When examining the microscopy images it can be concluded that biofilms are more easily formed with L. monocytogenes than E. coli O157:H7. Imaging also allowed for a visual representation of the remaining organisms that made it appear as if there was actually more bacteria recovery when the M-Vac sampling method was employed than when the sponge method was utilized.
Keywords: Environmental sampling; M-Vac; Sponge; Swab; Flocked Swab; Agriculture, Food Science and Technology (0359)